The influence of cerebellum on visual selective attention in patients with multiple lacunar cerebral infarction and its neuromodulatory mechanisms - Yuan, Xiaodong; Duan, Liqin; Ou, Ya; Ling, Qirong; Wang, Jing; Zhang, Jian; Cao, Lingyun; Qian, Hongchun; Zhang, Pingshu (Frontiers in Human Neuroscience, 2024)
Objective: this study aims to investigate the influence of the cerebellum on visual selective attention function and its neuromodulatory mechanism in patients with multiple lacunar cerebral infarction (MLCI).Methods: a retrospective analysis was conducted on 210 patients admitted with MLCI from January 2016 to May 2022. Analysed the electrophysiological characteristics of the P3a and P3b components of vision in both groups, as well as source reconstruction simulations of dipole activation in the brains of the two groups, and analysed the brain regions with differences in activation strength between the two groups.Results: this study found that there was no significant difference in peak amplitude between the two groups, but compared with the control group, the peak latency of the case group was significantly prolonged. Specifically, the P3a peak latency induced by the novel stimulus was longer than that induced by the target stimulus P3b peak latency. Source reconstruction results showed decreased and increased activation in several brain regions in the case group compared to the control group.Conclusion: the study suggests that the impairment of distracted attention capture is more pronounced in patients with MLCI. The cerebellum indirectly influences the ventral and dorsal frontoparietal attention networks by modulating the levels of excitation and inhibition within the cerebral cortex of the attention network. This may represent a potential mechanism through which the cerebellum regulates visual